If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3x + -3(4x + -8) = 14 Reorder the terms: 4x + -3x + -3(-8 + 4x) = 14 4x + -3x + (-8 * -3 + 4x * -3) = 14 4x + -3x + (24 + -12x) = 14 Reorder the terms: 24 + 4x + -3x + -12x = 14 Combine like terms: 4x + -3x = 1x 24 + 1x + -12x = 14 Combine like terms: 1x + -12x = -11x 24 + -11x = 14 Solving 24 + -11x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -11x = 14 + -24 Combine like terms: 24 + -24 = 0 0 + -11x = 14 + -24 -11x = 14 + -24 Combine like terms: 14 + -24 = -10 -11x = -10 Divide each side by '-11'. x = 0.9090909091 Simplifying x = 0.9090909091
| 50.01=(4.42)(h)+(3.41)(3-h) | | 123456789+123456789= | | 1-5y+4=2y+11-5y | | 5x+10=8x-3 | | 29=7y-6 | | 3(5x+2)=35 | | 4x+3x+4x= | | 10.45+x+-5=1.45 | | 10.45+-5=1.45 | | x/3-1-2 | | 4x=/3=8 | | 3x-2+x+6+34=360 | | X/15=4/X | | 5x-10=-7x+2 | | 35p-5=6p-18 | | 2x(3-4k)=pfork | | y=-8/9x-16 | | Y^(3/2)=5y | | 100-3y=5y-28 | | -6(-5x+3)=42 | | -7x+4x+6=-27 | | 16x-12+8x=14x+8 | | F(x)=2x/2-8x-10 | | 2x*3-5=5 | | -2x+1=-39 | | 5x^4+3x^2+2=0 | | 2h^2-3=15 | | 23.6/5.9 | | 10000xsquare-64=0 | | 3h-10=25 | | y=9+5x | | 144=12k |